World Happiness Report - Shatdal Chaudhary (Journal of Universal College of Medical Sciences, 2023)
Happiness is the main goal which most people and policy makers seek to ﬁnd. The idea of happiness is as old as human civilization. The concept of happiness has been the core of ancient Hindu and Greek cultures.  Deﬁnition of happiness can vary from person to person. Usually, happiness is deﬁned as an emotional state characterized by feelings of joy, satisfaction, contentment and fulﬁllment. Multiple approaches by various researchers lead to numerous measures of happiness such as the PANAS scale, subjective happiness scale, Oxford happiness inventory and Seligman's PERMA model. Happiness correlates negatively with morbidity, mortality, stress and anxiety in contrast to a positive correlation with motivation, healthy behaviours and longevity. One should enjoy what they are doing rather than falling into the trap of endless accumulation of wealth.